Effect of Brain Gym on the Short-Term Memory of Medical Students at the University of Nusa Cendana - Hamidah, Annisa Nur; Riwu, Magdarita; Manafe, Derry Tallo; Kareri, Dyah Gita Rambu (Cendana Medical Journal, 2024)
Background: The implementation of social and physical distancing during the COVID-19 pandemic has evidently limit the exercise or physical activity which could potentially have a long-term impact on health. In addition, few groups of students find it difficult to understand online classes, especially medical students who are known to have demanding learning schedule, therefore required to have supportive cognitive functions. Cognitive function, especially short-term memory, that students required in their learning activities could be improved in various ways, one of which is by doing brain gym exercise. Object: This study aims to analyze the effect of brain gym on short-term memory of students of the Faculty of Medicine, University of Nusa Cendana. Methods: The research method used in this study is Quasi Experimental with One Group Pre-Post Test design which was conducted on 54 preclinical students of the Faculty of Medicine, University of Nusa Cendana who fulfilled the inclusion and exclusion criteria. The samples were chosen using purposive sampling technique and were divided into an intervention group and a control group. The intervention group had received brain gym 3 times per week for 2 weeks with 10-15 minutes duration for each exercise. This study uses the Digit Span Test for short-term memory measurement before and after intervention followed by analysis using Paired t-test and Independent sample t-test. Results: The increase in short-term memory scores was experienced by both groups, but the control group did not indicate a significant difference. The significant difference was only appeared in the short-term memory score of the intervention group which was represented by the results of the Paired t-test analysis with p value = 0.000 (p < 0.05), while in the control group with the same analysis test indicated p value = 0.314 (p < 0.05). Most of the respondents had high short-term memory function before and after the intervention. Conclusion: There is a significant effect of doing brain gym on short-term memory in students of the Faculty of Medicine, University of Nusa Cendana. Keywords: Brain gym; short-term memory; medical students